Robotic rectal resection preserves anorectal function: Systematic review and meta‐analysis. Issue 6 (9th September 2021) - Grass, Julia K.; Chen, Chien‐Chih; Melling, Nathaniel; Lingala, Bharathi; Kemper, Marius; Scognamiglio, Pasquale; Persiani, Roberto; Tirelli, Flavio; Caricato, Marco; Capolupo, Gabriella T.; Izbicki, Jakob R.; Perez, Daniel R.
Abstract: Background: Improving survival rates in rectal cancer patients has generated a growing interest in functional outcomes after total mesorectal excision (TME). The well‐established low anterior resection syndrome (LARS) score assesses postoperative anorectal impairment after TME. Our meta‐analysis is the first to compare bowel function after open, laparoscopic, transanal, and robotic TME. Methods: All studies reporting functional outcomes after rectal cancer surgery (LARS score) were included, and were compared with a consecutive series of robotic TME ( n = 48). Results: Thirty‐two publications were identified, including 5 565 patients. Anorectal function recovered significantly better within one year after robotic TME (3.8 [95%CI –9.709–17.309]) versus laparoscopic TME (26.4 [95%CI 19.524–33.286]), p = 0.006), open TME (26.0 [95%CI 24.338–29.702], p = 0.002) and transanal TME (27.9 [95%CI 22.127–33.669], p = 0.003). Conclusions: Robotic TME enables better recovery of anorectal function compared to other techniques. Further prospective, high‐quality studies are needed to confirm the benefits of robotic surgery.